(untitled) (Palíndromo, 2013)
This article is a reflection on educational practices held in museums and art spaces. The text will work with the museum structure in general, bringing some historical aspects of this institution. This raises the possibility of social role that the museum can play, reflecting the reason people attend these spaces and realizing the framework that predisposes museums. From an understanding of the social and educational characteristic of these institutions is what brings the contribution of Lev S. Vygotsky to the practice of education in art museums. Understood as cultural mediation, the education in exhibitions suggests for there to be a dialogue relationship between the mediator, the work and the public.